Estimation of reliability of street lighting systems - Сапрыка, Александр Викторович (Eastern-European Journal of Enterprise Technologies, 2013)
The article represents an estimation of the reliability of street lighting system. The modern system of street lighting is the most complex system, the reliability of which is determined by the ability of an object to perform specified functions, saving in the course of time the values of specified operational characteristics within limits that match the specified modes and conditions of use. The process of change of operating mode parameters in the system of street lighting is usually accidental. This is connected with the random nature of load changes and the corresponding random nature of changes of power quality. The reliable operation of lighting systems is of great importance in the common balance of power consumption, that is why the modeling of the reliability of operation of shedding devices is relevant. A model of the reliability of LED shedding devices was suggested, taking into account the schedule of cycling work of lighting devices and monthly temperature and the prospects for further improvement of the street lighting of the city.